2022
DOI: 10.1038/s41467-022-35297-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell profiling of healthy human kidney reveals features of sex-based transcriptional programs and tissue-specific immunity

Abstract: Knowledge of the transcriptional programs underpinning the functions of human kidney cell populations at homeostasis is limited. We present a single-cell perspective of healthy human kidney from 19 living donors, with equal contribution from males and females, profiling the transcriptome of 27677 cells to map human kidney at high resolution. Sex-based differences in gene expression within proximal tubular cells were observed, specifically, increased anti-oxidant metallothionein genes in females and aerobic met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 117 publications
7
20
0
Order By: Relevance
“…Our analysis of thymic cell gene expression uncovers that female-derived stromal, epithelial, and T cells have significant upregulation of metabolic, translation, and antigen presentation pathways whereas male cells have increased adipogenesis, proinflammatory signaling, and glucocorticoid signaling. These differences in cell metabolism align with current literature describing transcript-level sex differences in other organs [41][42][43] and highlight the need for sex-based cell culture optimization to meet differential cell growth and differentiation requirements in in vitro T cell culture systems.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our analysis of thymic cell gene expression uncovers that female-derived stromal, epithelial, and T cells have significant upregulation of metabolic, translation, and antigen presentation pathways whereas male cells have increased adipogenesis, proinflammatory signaling, and glucocorticoid signaling. These differences in cell metabolism align with current literature describing transcript-level sex differences in other organs [41][42][43] and highlight the need for sex-based cell culture optimization to meet differential cell growth and differentiation requirements in in vitro T cell culture systems.…”
Section: Discussionsupporting
confidence: 80%
“…In addition to these changes common to other organs 40,41 , we identify meaningful thymus-specific differences which could significantly affect key processes in the development and training of thymocytes. Females have a larger proportion of cortical cells per lobule which aligns with known slower rates of thymic involution in females leading to a larger cortex/medulla ratio 26,27,59 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that although sexbiased expression evolves fast at the gene level, it evolves more slowly at the cell-type level. This is consistent with a single-cell study of the human kidney (46) that also identified the proximal tubule cells as being sexually dimorphic and driving most sex dimorphisms despite there being very little conservation in the set of sex-biased genes between rodents and humans.…”
Section: Conservation Of the Sexually Dimorphic Cell Typessupporting
confidence: 88%
“…Aggregation of these samples yielded 80,634 cells from snRNA-seq and 120,679 cells from snATAC-seq. We could still clearly detect KIM1 +/ VCAM1 + FR proximal tubule cells even when clustering cells solely from living donor kidney biopsies, consistent with recent analysis of living donor kidneys (37), indicating that tumor mass effect alone does not explain FR-PTC accumulation (Figure 1E, Supplemental Figure 3A-D). More broadly, cell type-specific RNA expression and ATAC accessibility profiles were similar between living donor kidney biopsies and nephrectomy samples (Figure 1F, Supplemental Figure 3E).…”
Section: Resultssupporting
confidence: 89%